PENENTUAN KADAR KIO3 DALAM GARAM KONSUMSI SECARA SPEKTOFOTOMETRI - A.H., Andriati
Abstract : Spectrophotometric method could be used for anaysis of potassium iodate. Potassium iodate was reduced by an excess of potassium iodide in an acid solution which produced iodine and could form a stable blue colour with amylum. The effect of concentration related to phosphoric acid, potassium iodide, amylum and sodium chloride was studied for obtain optimum condition. Analysis potassium iodate from seven samples with the different trade mark was then determined using such optimum condition. The research result showed 42.92 ppm; 63.16 ppm; 58.30 ppm; 26.92 ppm; 14.04 ppm; 85.69 ppm and 57.08 ppm potassium iodate content in salt sample respectivelly. Comparing with titrimetric method it was shown that the potassium iodate content were not significantly different except that the means value of salt sample number five was of obviously different. Statistically, spectrophotometric method had high precision and sensitivity with detection limit was 0.026 ppm. The sulphat, calsium and magnesium ions, water content and insoluble water content were proven to be in conformity with the maximum consumption salt standard based on Indonesian National Standard (according to SNI-01-3556-1994).